COMPARISON OF EFFICIENCY SCHOOL PERFORMANCE BETWEEN NATURAL AND SOCIAL SCIENCES: A BOOTSTRAPPING DATA ENVELOPMENT ANALYSIS - Zaenal Mustakim; Muhamad Chamdani; Umi Mahmudah (LPMPP Universitas Negeri Yogyakarta, 2019)
The main purpose of this study is to compare the efficiency performance of high school education in Indonesiabased on its specialization groups, namely natural and social sciences. This study uses secondary data of high school published by Ministry of Education and Culture of Republic of Indonesia in 2016 which covers general description such as the numbers of schools, students, teachers, graduates, classes, et cetera. This study uses a bootstrap approach that is applied in Data Envelopment Analysis (DEA) method, which compares the efficiency of each Decision Making Unit (DMU). To compare its efficiency, as many as 34 provinces are used as DMUs by using six input variables, namely the number of participants of national exam, students, schools, teachers, libraries, and the number of classrooms. The output variables are the number of graduates, the average score of national exam in Indonesian, English, and mathematics.The results indicate that all provinces have very good performance in organizing high school education for both natural and social sciences where the average efficiency scores of the traditional DEA are .99 and .98 for natural and social sciences, respectively. Meanwhile, its average scores from bootstrapped DEA are .98 and .96 for natural and social sciences, respectively. The empirical results also reveal that bootstrapped DEA provides better accuracy of efficiency scores than the traditional DEA. Overall, the provinces in Indonesia have better performance in organizing natural science than social science.